Teachers' conceptions of competency assessment and modular certification (CAMC): Assessment of the measurement model - Lee, L.H.; Jamaluddin, S. (2008)
Competency Assessment and Modular Certification (CAMC) was introduced in line with the introduction of 22 vocational subjects in secondary schools in Malaysia since 2002. Teachers' conceptions of CAMC were considered important as it was determined as one of the factors that may influence CAMC implementation. The purpose of this study was to test empirically using Structural Equation Modeling (SEM) approach the Confirmatory Factor Analysis (CFA) model of teachers' conceptions of CAMC. The teachers' conceptions of CAMC measured such dimensions as improve student learning, student accountability, and school accountability. Sample for the study were 205 teachers selected from schools offering the vocational subjects in Kuala Lumpur, Selangor, Melaka, Negeri Sembilan, and Perak. The instrument consisted of 11 items and the items were hypothesized a priori to have nonzero loadings on the three dimensions. Analysis of the 11 items resulted in a well-fitting model (x2 = 72.38; df = 41; GFI = .941; CFI = .939; RMSEA = .061). The final fitted measurement model was further validated.